Manajemen Pendidikan Dalam Pandangan Al-Qur’an - Arif Rahman Aziz; Dede Asiah; Irfan Afandi; Pipin Pitriyani; Rama Aditya; Yayat Hidayat (Peneliti.net, 2022)
Al-Qur'an as the main source of Islam contains a myriad of wisdom that serves to guide the path of human life. At the time of the Prophet Muhammad SAW., life, the substance of the Qur'an he practiced himself and he taught his friends. In addition to the Qur'an, the actions, words and attitudes of the Prophet Muhammad SAW are also a reference in Muslim life, both concerning relationships with God, fellow humans and nature. This is what is called a hadith. Al-Qur'an is used as a source of Islamic education and other sciences, including management of Islamic education, because the Qur'an has absolute values that are derived from Allah SWT. Allah SWT created humans and it is he who educates humans, so that the content of education has been contained in His revelations. There is not a single problem, including the issue of Islamic education management that escapes the reach of the Koran.